A Phenotypic Comparison between HIV Positive and HIV Negative Tuberculous Meningitis Patients - Anggraini, Ita; Hartantri, Yovita; Rizal, Ahmad (Makara Journal of Health Research, 2017)
Background: Tuberculous meningitis (TBM) is the most common type of meningitis found in humans and the Human Immunodeficiency Virus (HIV) is a major risk factor of TBM. This study aimed to identify phenotype differences, such as clinical manifestations, cerebrospinal fluid (CSF) findings, and chest x-ray results between HIV positive and HIV negative TBM patients. Methods: This was a comparative analytical study of 123 TBM patients. The patients were divided into two groups based on their HIV status, and their phenotypes were compared. A retrospective cross sectional designed study was carried out in case report form using a TBM cohort and Rifampicin dose finding study in the neurological ward at the Dr. Hasan Sadikin General Hospital Bandung, between January 2015 and August 2016. Categorical data was analysed using Chi square tests and the alternative Fisher’s Exact test and Mann-Whitney test was used for numerical data. P-values were significant if p < 0.05. Results: Of the phenotypic parameters, only the CSF results had statistical difference. HIV positive subjects had higher CSF to blood glucose ratios (0.42 vs. 0.18; p = 0.001) and fewer leukocyte cells (41 vs. 199; p < 0.001). Conclusions: CSF findings of TBM patients’ revealed differences between HIV positive and negative patients, whilst clinical manifestations and chest x-ray results showed no differences.